Eksplorasi Tumbuhan Pteridophyta dan Bryophyta di Air Terjun Purba Tirai Bidadari Tiris Probolinggo dan Pemanfaatannya Sebagai Media Flipbook Pada Submateri Plantae Kelas X SMA/MA - Lailatul Lutfiah; Bayu Sandika (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Waterfalls are closely related to biodiversity because the surrounding ecosystems are diverse, such as having variations in humidity, temperature and light that support various species of plants and animals. These plants are generally found in humid environments, but not in snowy or dry areas. However, the diversity of Bryophyta and Pteridophyta in this area is still limited and has not been systematically documented. The objectives of the study were 1) To determine the types of Pteridophyta and Bryophyta diversity in the Tiris Probolinggo Curtain Ancient Waterfall and 2) To determine the validity of the Pteridophyta and Bryophyta Flipbook in the Tiris Probolinggo Curtain Ancient Waterfall. This study uses a qualitative approach with a descriptive explorative type. The exploration method is applied to find and identify Pteridophyta and Bryophyta in the Tiris Tiris Curtain Ancient Waterfall area. Data were collected through observation, identification, documentation, validation questionnaires, and laboratory tests on plant samples. Identification was carried out using reference books (Gembong Tjitrosoepomo), Flora (Dr. C. G.G.J, van Steenis, et al.), Plannet application, Google Lens, internet, and journals. Validation of identification by botanists, while validation of flipbooks was seen through constructs or contents by involving media and material experts consisting of two validators each. The results of the study showed 1) there were 41 species of Pteridophyta with 8 Families and 31 genera, the results of validation by botanists were 92% and 18 species of Bryophyta with 15 families and 14 genera, the results of validation were 90.2%, both in the very valid category. 2) The validity of the flipbook by media experts reached 91% and material experts 94%, also in the very valid category. From the average results above, it can be concluded that the flipbook that has been compiled based on the results of identification of Pteridophyta and Bryophyta plants in the Tiris Probolinggo Curtain Ancient Waterfall is declared very feasible.